Buku-buku Terbaru dalam Kajian Disabilitas - Inklusi, Jurnal (INKLUSI, 2019)
Dalam review kali ini, editor Jurnal INKLUSI memilih lima buku terbaru dalam kajian disabilitas untuk diperkenalkan kepada sidang pembaca sekalian. Lima buku dimaksud adalah: The Palgrave Handbook of Disability and Citizenship in the Global South Author(s): Brian Watermeyer, Judith McKenzie, Leslie Swartz Publisher: Springer International Publishing;Palgrave Macmillan, Year: 2019 ISBN: 978-3-319-74674-6;978-3-319-74675-3 Prevention of Chronic Diseases and Age-Related Disability Author(s): Jean-Pierre Michel Series: Practical Issues in Geriatrics Publisher: Springer International Publishing, Year: 2019 ISBN: 978-3-319-96528-4,978-3-319-96529-1 Accessible America: A History of Disability and Design Author(s): Bess Williamson Publisher: New York University Press, Year: 2019 ISBN: 1479894095,9781479894093 The Science and Politics of Work Disability Prevention Author(s): Ellen MacEachen (ed.) Publisher: Routledge, Year: 2019 ISBN: 9781138335318, 9781138335301 The Routledge Handbook of Disability Arts, Culture, and Media Author(s): Bree Hadley, Donna McDonald Series: Routledge International Handbooks Publisher: Routledge, Year: 2019 ISBN: 9780815368410, 9781351254687 Deskripsi lengkap silakan unduh versi PDF.